1998
DOI: 10.1063/1.122000
|View full text |Cite
|
Sign up to set email alerts
|

Thin multiplication region InAlAs homojunction avalanche photodiodes

Abstract: Low excess noise in avalanche photodetectors (APDs) is desired for improved sensitivity and high-frequency performance. Gain and noise characteristics are measured for InAlAs p-i-n homojunction APDs that were grown with varying i-region widths on InP by molecular beam epitaxy. The effective ionization ratio k (β/α) determined by noise measurements shows a dependence on multiplication region width, reducing from 0.31 to 0.18 for multiplication region thicknesses of 1600–200 nm. This trend follows previously sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(36 citation statements)
references
References 12 publications
5
29
1
Order By: Relevance
“…Since this ratio is a material property, for a given electric field, efforts to improve the APD performance have focused on optimizing the electric field profile and characterizing new materials. Recently, lower multiplication noise and higher gainbandwidth products have been achieved by sub micrometer scaling of the thickness of the multiplication region [4][5][6][7][8][9][10][11][12]. This is in direct contrast to what would have been predicted by the local-field model and is due to the nonlocal nature of impact ionization, which can be neglected if the thickness of the multiplication region is much greater than the "dead length", the distance over which carriers gain sufficient energy to impact ionize.…”
Section: Introductioncontrasting
confidence: 43%
“…Since this ratio is a material property, for a given electric field, efforts to improve the APD performance have focused on optimizing the electric field profile and characterizing new materials. Recently, lower multiplication noise and higher gainbandwidth products have been achieved by sub micrometer scaling of the thickness of the multiplication region [4][5][6][7][8][9][10][11][12]. This is in direct contrast to what would have been predicted by the local-field model and is due to the nonlocal nature of impact ionization, which can be neglected if the thickness of the multiplication region is much greater than the "dead length", the distance over which carriers gain sufficient energy to impact ionize.…”
Section: Introductioncontrasting
confidence: 43%
“…Additionally, previous studies have shown that the addition of Al to a material does not significantly increase its k-value, as with AlAsSb 28 and InAlAs. 23 Furthermore, initial Monte Carlo studies indicate that a high hole scattering rate may contribute further to the low k-value.…”
Section: Performance and Analysismentioning
confidence: 99%
“…The dark current at 95% breakdown is ~ 350 nA, which is approximately 100x lower than that of Ge on Si APDs [18][19][20] and comparable to that of AlInAs/InGaAs APDs. 15,23 The step in the photocurrent near -38 V occurs when the edge of the depletion region reaches the absorbing layer, which is referred as punch-through. The gain is plotted on the right vertical axis.…”
Section: Performance and Analysismentioning
confidence: 99%
“…In determining its gain, multiplication noise, and the gain-bandwidth product, the multiplication region of an APD plays a critical role. Sub-micron scaling [15][16][17][18][19][20][21][22][23][24] of the thickness of the multiplication region has been found to give lower multiplication noise and higher gain-bandwidth products in APDs. This is due to the non-local nature of impact ionization, which can be neglected if the thickness of the multiplication region is much greater than the "dead length", which is the minimum distance carriers travel to gain sufficient energy to impact ionize.…”
Section: Long-wavelength Impact-ionization-engineered Avalanche Photmentioning
confidence: 99%